2020
DOI: 10.1021/acsomega.0c04365
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Dependent Photoluminescence of Europium(III) Coordination Oligomeric Silsesquioxane: Synthesis and Mechanism

Abstract: The coordination environment of Eu3+ is a crucial factor in the optical performance of the complex. Herein, a new kind of oligomeric silsesquioxane was employed to improve the coordination environment of central ions, the luminescence intensity of which was greatly enhanced with an efficient emission peak at 619 nm. More importantly, the photoluminescent properties of the product will be altered because of the formation of the Si–O–Si structure. The relevant mechanism has also been investigated and proposed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…Like the C spectrum, the binding energy of C═O has also decreased(−0.023 eV), but the binding energy of C-O has increased(0.006 eV). [38] The results showed that H + could catalyze the ligand, and the coordination mode of BTA with rare earth ions changed from the original chelating bidentate coordination to monodentate coordination mode, which reduced the energy transfer efficiency between the ligand and rare earth ions. [39]…”
Section: Acid Rain Detection Mechanismmentioning
confidence: 98%
“…Like the C spectrum, the binding energy of C═O has also decreased(−0.023 eV), but the binding energy of C-O has increased(0.006 eV). [38] The results showed that H + could catalyze the ligand, and the coordination mode of BTA with rare earth ions changed from the original chelating bidentate coordination to monodentate coordination mode, which reduced the energy transfer efficiency between the ligand and rare earth ions. [39]…”
Section: Acid Rain Detection Mechanismmentioning
confidence: 98%
“… 4 One of the RE 3+ ions that consists of partially filled f-orbitals and is highly efficient in the red region is Europium (Eu 3+ ). 5 On the other hand, TM ions are a group of elements characterized by their partially filled d-orbitals, or the ability to form such orbitals. One such TM ion is Manganese (Mn) in its 4+ state and is known for its efficient far-red emission.…”
Section: Introductionmentioning
confidence: 99%